2013
DOI: 10.1002/erv.2223
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption and Pancreatic Function are Preserved in Anorexia Nervosa Patients in Both a Severely Malnourished State and After Recovery

Abstract: In this series, there was neither intestinal absorption nor pancreatic function disturbances in severely malnourished AN patients either before or after weight recovery. The usefulness of these tests in the differentiation of functional versus structural changes needs further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 30 publications
(45 reference statements)
0
30
0
Order By: Relevance
“…This finding supports the clinical observation that sepsis is in fact an uncommon occurrence in patients with AN. This contrast between starvation because of AN, compared with other etiologies, suggests the presence of, as yet unidentified factors . Whereas impaired functionality has not been demonstrated, a controlled study (21 ANR; 15 AN‐BP; 20 controls) found that diamine oxidase, a marker for intestinal villi integrity and maturity, was significantly reduced in patients with ANR.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding supports the clinical observation that sepsis is in fact an uncommon occurrence in patients with AN. This contrast between starvation because of AN, compared with other etiologies, suggests the presence of, as yet unidentified factors . Whereas impaired functionality has not been demonstrated, a controlled study (21 ANR; 15 AN‐BP; 20 controls) found that diamine oxidase, a marker for intestinal villi integrity and maturity, was significantly reduced in patients with ANR.…”
Section: Resultsmentioning
confidence: 97%
“…Low grade chronic injury is thought to explain the pseudocyst formation reported in two case reports and the elevation of elastase‐1 . A study that examined pancreatic function based on fecal elastase measurements in nine severely malnourished patients with AN (7 restrictors; 3 binge‐ purge), at the time of admission and then when weight restored, could find no evidence of pancreatic dysfunction through measurement of fecal elastase and digestion of 13 C‐labelled triglycerides . These studies report conflicting evidence as to the prevalence of baseline pancreatic dysfunction in the context of severe wasting because of AN, which might predispose the compromised pancreas to more severe injury if challenged by other factors.…”
Section: Resultsmentioning
confidence: 99%
“…Not even AN with severe underweight has demonstrated mucosal atrophy. 10,32 In addition, data on ethnicity and diet were lacking. The latter prevented us from studying whether strict adherence to a gluten-free diet mediated the association with AN.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…3 Approximately 50% of patients with anorexia nervosa have evidence of zinc deficiency. 4 Zinc deficiency can lead to deficient immune response owing to its importance as a secondary messenger in lymphocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%